Adhesive laminated core for stator
Patent Information
- Application Number
- JP2022197344
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-17
- Filing Date
- 2022-12-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-12-17
AI Technical Summary
Existing technologies face issues with adhesive strength in laminated cores for stators, leading to stress concentration and separation of insulating coatings due to adhesive shrinkage, which affects both adhesive strength and magnetic properties.
A laminated core design with specific thickness ratios and positioning of insulating and adhesive layers, adhering to the equation -4.3×t1+3.6≦t2≦-4.3×t1+6.9, ensuring adequate adhesive strength and preventing insulating coating peeling while maintaining magnetic properties.
The solution effectively prevents insulating coating peeling and maintains magnetic properties by optimizing adhesive thickness and positioning, enhancing both mechanical strength and magnetic performance.
Smart Images

Figure 00000015_0000 
Figure 00000016_0000 
Figure 00000017_0000
Abstract
Description
[Technical Field]
[0001] The present invention relates to an adhesive laminated core for a stator. This application claims priority based on Japanese Patent Application No. 2018-235864, filed on December 17, 2018, the contents of which are incorporated herein by reference. [Background technology]
[0002] Conventionally, laminated cores such as those described in Patent Document 1 below have been known. Patent Document 1 below discloses a direct drive motor with a stator coaxially arranged inside a rotor. An insulating coating and an adhesive coating are formed on the electromagnetic steel sheet on the stator side. It is described that if the insulating coating is thinner than 0.80 μm, sufficient insulation capacity cannot be obtained, and if it is thicker than 1.20 μm, excitation efficiency is poor. On the other hand, it is described that if the adhesive coating is thinner than 1.80 μm, sufficient adhesion capacity cannot be obtained, and if it is thicker than 2.20 μm, excitation efficiency is poor. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 2015-12756 Summary of the Invention [Problem to be solved by the invention]
[0004] Applying a thin layer of adhesive to thin the bonded area increases the proportion of the electromagnetic steel sheets in the laminated core. However, as noted in Patent Document 1, if the bonded area is too thin, the adhesive strength decreases. Therefore, it is conceivable to use a softer adhesive to form a softer bonded area while still ensuring adhesive strength. However, in this case, the force applied when the adhesive hardens and shrinks causes stress concentration in the insulating coating, making it more likely to peel off from the electromagnetic steel sheets. The technology disclosed in Patent Document 1 does not recognize this issue, and naturally cannot solve it.
[0005] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive laminated core for a stator that can prevent peeling of an insulating coating and suppress deterioration of magnetic properties due to stress applied to an electromagnetic steel sheet by an adhesive joint, and a rotating electric machine equipped with this adhesive laminated core for a stator. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention employs the following means. (1) One aspect of the present invention is an adhesive laminated core for a stator, comprising a plurality of electromagnetic steel sheets having a phosphate-based insulating coating on the surface and stacked coaxially, and adhesive joints provided between the electromagnetic steel sheets, wherein the average thickness of the insulating coating is 0.3 μm to 1.2 μm, the average thickness of the adhesive joints is 1.0 μm to 3.0 μm, and when the average thickness of the insulating coating is t1 in μm and the average thickness of the adhesive joints is t2 in μm, the following formula 1 is satisfied, and the adhesive joints are positioned corresponding to the teeth of the stator. -4.3×t1+3.6≦t2≦-4.3×t1+6.9 (Formula 1)
[0007] (2) In the aspect described in (1) above, the following configuration may be adopted: the adhesive portion is disposed at at least one of the tip position of the tooth portion and the boundary position between the core back portion and the tooth portion.
[0008] (3) In the embodiment described in (1) or (2) above, the following configuration may be adopted: adjacent adhesive portions are spaced apart from each other. [Effects of the Invention]
[0009] According to the above aspects of the present invention, it is possible to provide an adhesive laminated core for a stator that can prevent peeling of the insulating coating and suppress deterioration of magnetic properties due to stress applied to the electromagnetic steel sheet by the adhesive joint, and a rotating electric machine that includes this adhesive laminated core for a stator. [Brief explanation of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view of a rotating electrical machine including a stator bonded laminated core according to an embodiment of the present invention. [Figure 2] FIG. 2 is a side view of the stator laminated core. [Figure 3] 3 is a cross-sectional view taken along the line AA in FIG. 2, showing an example of a pattern of adhesive portions formed in the adhesive laminated core for a stator. FIG. [Figure 4] FIG. 1 is a side view of a manufacturing apparatus used to manufacture an example of a stator bonded laminated core. [Figure 5] 10 is a graph showing the relationship between the average thickness t1 of the insulating coating and the average thickness t2 of the adhesive joint in the same example. [Figure 6] 10 is a graph showing the relationship between the average thickness t1 of the insulating coating and the average tensile modulus E of the adhesive joint in the example. DETAILED DESCRIPTION OF THE INVENTION
[0011] Hereinafter, with reference to the drawings, a stator adhesive laminated core according to one embodiment of the present invention and a rotating electric machine equipped with this stator adhesive laminated core will be described. Note that in this embodiment, the rotating electric machine will be described as an electric motor, specifically an AC motor, more specifically a synchronous motor, and even more specifically a permanent magnet field motor. This type of electric motor is suitable for use in, for example, electric vehicles.
[0012] 1, the rotating electric machine 10 includes a stator 20, a rotor 30, a case 50, and a rotating shaft 60. The stator 20 and the rotor 30 are housed in the case 50. The stator 20 is fixed within the case 50. In this embodiment, the rotating electric machine 10 is an inner rotor type in which the rotor 30 is located radially inside the stator 20. However, the rotating electric machine 10 may also be an outer rotor type in which the rotor 30 is located outside the stator 20. Also, in this embodiment, the rotating electric machine 10 is a three-phase AC motor with 12 poles and 18 slots. However, the number of poles, the number of slots, the number of phases, etc. can be changed as appropriate. The rotating electrical machine 10 can rotate at a rotation speed of 1000 rpm by applying an excitation current of, for example, an effective value of 10 A and a frequency of 100 Hz to each phase.
[0013] The stator 20 includes a stator adhesive laminated core (hereinafter referred to as a stator core) 21 and a winding (not shown). The stator core 21 includes an annular core back portion 22 and a plurality of teeth portions 23. Hereinafter, the direction of the central axis O of the stator core 21 (or the core back portion 22) will be referred to as the axial direction, the radial direction of the stator core 21 (or the core back portion 22) (the direction perpendicular to the central axis O) will be referred to as the radial direction, and the circumferential direction of the stator core 21 (or the core back portion 22) (the direction going around the central axis O) will be referred to as the circumferential direction.
[0014] The core back portion 22 is formed in an annular shape when viewed in a plan view of the stator 20 in the axial direction. The multiple teeth 23 protrude radially inward from the inner periphery of the core back portion 22 (toward the central axis O of the core back portion 22 along the radial direction). The multiple teeth 23 are arranged at equal angular intervals in the circumferential direction. In this embodiment, 18 teeth 23 are provided at central angle intervals of 20 degrees around the central axis O. The multiple teeth 23 are formed to have the same shape and size as one another. Therefore, the multiple teeth 23 have the same thickness dimension as one another. The winding is wound around the teeth 23. The winding may be a concentrated winding or a distributed winding.
[0015] The rotor 30 is disposed radially inside the stator 20 (stator core 21). The rotor 30 includes a rotor core 31 and a plurality of permanent magnets 32. The rotor core 31 is formed in an annular (circular ring) shape and is arranged coaxially with the stator 20. The rotating shaft 60 is arranged inside the rotor core 31. The rotating shaft 60 is fixed to the rotor core 31. The permanent magnets 32 are fixed to the rotor core 31. In this embodiment, a pair of permanent magnets 32 forms one magnetic pole. The pairs of permanent magnets 32 are arranged at equal angular intervals in the circumferential direction. In this embodiment, 12 pairs of permanent magnets 32 (24 in total) are provided at central angle intervals of 30 degrees around the central axis O.
[0016] In this embodiment, an interior permanent magnet motor is used as the permanent magnet field motor. A rotor core 31 is formed with a plurality of through holes 33 that pass through the rotor core 31 in the axial direction. The plurality of through holes 33 are provided corresponding to the arrangement of a plurality of permanent magnets 32. Each permanent magnet 32 is fixed to the rotor core 31 while being disposed in the corresponding through hole 33. Each permanent magnet 32 can be fixed to the rotor core 31, for example, by bonding the outer surface of the permanent magnet 32 to the inner surface of the through hole 33 with an adhesive. Note that a surface permanent magnet motor may be used as the permanent magnet field motor instead of the interior permanent magnet type.
[0017] Both the stator core 21 and the rotor core 31 are laminated cores. For example, as shown in Fig. 2, the stator core 21 is formed by laminating a plurality of electromagnetic steel plates 40 in a lamination direction. The lamination thickness (total length along the central axis O) of each of the stator core 21 and the rotor core 31 is, for example, 50.0 mm. The outer diameter of the stator core 21 is, for example, 250.0 mm. The inner diameter of the stator core 21 is, for example, 165.0 mm. The outer diameter of the rotor core 31 is, for example, 163.0 mm. The inner diameter of the rotor core 31 is, for example, 30.0 mm. However, these values are merely examples, and the lamination thickness, outer diameter, and inner diameter of the stator core 21 and the lamination thickness, outer diameter, and inner diameter of the rotor core 31 are not limited to these values. Here, the inner diameter of the stator core 21 is based on the tip ends of the teeth 23 of the stator core 21. In other words, the inner diameter of the stator core 21 is the diameter of an imaginary circle inscribed in the tip ends of all of the teeth 23.
[0018] Each of the electromagnetic steel sheets 40 that form the stator core 21 and the rotor core 31 is formed, for example, by punching an electromagnetic steel sheet that serves as a base material. Known electromagnetic steel sheets can be used as the electromagnetic steel sheets 40. The chemical composition of the electromagnetic steel sheets 40, as shown below in mass %, contains 2.5% to 3.9% Si by mass. By setting the chemical composition within this range, the yield strength of each of the electromagnetic steel sheets 40 can be set to 380 MPa or more and 540 MPa or less.
[0019] Si: 2.5% to 3.9% Al: 0.001% to 3.0% Mn: 0.05% to 5.0% Remainder: Fe and impurities
[0020] In this embodiment, a non-oriented electrical steel sheet is used as the electrical steel sheet 40. As the non-oriented electrical steel sheet, a non-oriented electrical steel strip according to JIS C2552:2014 can be used. However, instead of the non-oriented electrical steel sheet, a grain-oriented electrical steel sheet may be used as the electrical steel sheet 40. In this case, as the grain-oriented electrical steel sheet, a grain-oriented electrical steel strip according to JIS C2553:2012 can be used.
[0021] In order to improve the workability of the stator core 21 (hereinafter sometimes referred to simply as the "laminated core") and the iron loss of the laminated core, both sides of the electromagnetic steel sheets 40 are coated with a phosphate-based insulating coating. Examples of materials that can be used to form the insulating coating include (1) inorganic compounds, (2) organic resins, and (3) mixtures of inorganic compounds and organic resins. Examples of inorganic compounds include (1) composites of dichromate and boric acid, and (2) composites of phosphate and silica. Examples of organic resins include epoxy resins, acrylic resins, acrylic styrene resins, polyester resins, silicone resins, and fluorine-based resins.
[0022] In order to ensure the insulating performance between the stacked magnetic steel sheets 40, the lower limit of the average thickness t1 of the insulating coating (average thickness per side of the magnetic steel sheets 40) is preferably 0.3 μm, more preferably 0.7 μm. On the other hand, as the insulating coating becomes thicker, the insulating effect saturates. Furthermore, as the insulating coating becomes thicker, the proportion of the magnetic steel sheets 40 in the laminated core decreases, and the performance of the laminated core deteriorates. Therefore, it is preferable that the insulating coating be as thin as possible while still ensuring sufficient insulating performance. The upper limit of the average thickness of the insulating coating (thickness per side of the magnetic steel sheets 40) is preferably 1.2 μm, more preferably 0.9 μm. The average thickness t1 of the insulating coating is the average value for the entire laminated core. The thickness of the insulating coating is designed to be almost the same regardless of the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness t1 of the insulating coating can be determined by the value measured at the top end of the laminated core.
[0023] As the thickness of the electromagnetic steel sheets 40 becomes thinner, the proportion of the laminated core occupied by the electromagnetic steel sheets 40 gradually decreases. Furthermore, as the electromagnetic steel sheets 40 become thinner, the manufacturing costs of the electromagnetic steel sheets 40 increase. Therefore, taking into consideration the decrease in the proportion of the laminated core occupied by the electromagnetic steel sheets 40 and the manufacturing costs, the lower limit of the average thickness of the electromagnetic steel sheets 40 is 0.15 mm, more preferably 0.18 mm. On the other hand, if the electromagnetic steel sheets 40 are too thick, the manufacturing cost will be favorable but the eddy current loss will increase and the core iron loss will deteriorate. Therefore, taking into consideration the core iron loss and manufacturing cost, the upper limit of the average thickness of the electromagnetic steel sheets 40 is 0.35 mm, more preferably 0.30 mm. An example of an average thickness of the electromagnetic steel sheet 40 that satisfies the above range is 0.20 mm. The average thickness of the electromagnetic steel sheet 40 also includes the thickness of the insulating coating.
[0024] As shown in FIG. 3 , the multiple electromagnetic steel sheets 40 that form the stator core 21 are stacked via adhesive joints 41 arranged at multiple points. Each adhesive joint 41 is an adhesive that hardens without being separated. To form the adhesive joints 41, for example, a thermosetting adhesive that uses polymerization bonding is used. As such an adhesive, in addition to a thermosetting adhesive, a radical polymerization adhesive or the like can also be used. From the viewpoint of productivity, it is desirable to use a room-temperature curing adhesive. A room-temperature curing adhesive hardens at 20°C to 30°C. An acrylic adhesive is preferred as the room-temperature curing adhesive. A typical acrylic adhesive is SGA (Second Generation Acrylic Adhesive). Anaerobic adhesives, instant adhesives, and elastomer-containing acrylic adhesives can all be used as long as they do not impair the effects of the present invention. Note that the adhesive referred to here refers to the state before hardening; after the adhesive hardens, it becomes the adhesive joints 41.
[0025] The average tensile modulus E of the adhesive joint 41 at room temperature (20°C to 30°C) is set to be in the range of 1500 MPa to 4500 MPa. If the average tensile modulus E of the adhesive joint 41 is less than 1500 MPa, a problem occurs in which the rigidity of the laminated core decreases. Therefore, the lower limit of the average tensile modulus E of the adhesive joint 41 is set to 1500 MPa, more preferably 1800 MPa. Conversely, if the average tensile modulus E of the adhesive joint 41 exceeds 4500 MPa, a problem occurs in which the insulating coating formed on the surface of the electromagnetic steel sheet 40 peels off. Therefore, the upper limit of the average tensile modulus E of the adhesive joint 41 is set to 4500 MPa, more preferably 3650 MPa.
[0026] The average tensile modulus E is measured by a resonance method, specifically in accordance with JIS R 1602:1995. More specifically, first, a sample for measurement (not shown) is produced. This sample is obtained by bonding two electromagnetic steel sheets 40 together with the adhesive to be measured and curing the adhesive to form a bonded joint 41. If the adhesive is a thermosetting type, this curing is performed by applying heat and pressure under heating and pressure conditions that are used in actual operation. On the other hand, if the adhesive is a room temperature curing type, this is performed by applying pressure at room temperature. The tensile modulus of elasticity of this sample is then measured by the resonance method. As described above, the measurement method for the tensile modulus of elasticity by the resonance method is performed in accordance with JIS R 1602:1995. Thereafter, the tensile modulus of elasticity of the adhesive joint 41 alone is determined by subtracting the influence of the magnetic steel sheet 40 itself from the tensile modulus of elasticity (measured value) of the sample through calculation.
[0027] The tensile modulus thus determined from the sample is equal to the average value for the entire laminated core, and this value is regarded as the average tensile modulus E. The composition is set so that the average tensile modulus E varies little with the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average tensile modulus E can also be determined by measuring the value of the cured adhesive joint 41 at the top end of the laminated core.
[0028] A method of bonding multiple electromagnetic steel sheets 40 can be used in which adhesive is applied in dots to the undersides (one side) of the electromagnetic steel sheets 40, the sheets are then stacked, and either or both of them are heated and pressed together. Any means may be used for heating, such as heating the stator core 21 in a high-temperature bath or electric furnace, or heating the stator core 21 by directly passing electricity through it. On the other hand, when a room-temperature curing adhesive is used, the sheets are bonded together by pressing alone without heating.
[0029] FIG. 3 shows an example of a pattern of the adhesive portions 41. Each adhesive portion 41 is located at a position corresponding to the tooth portion 23 of the stator 20. Each adhesive portion 41 is formed as a plurality of circular dots. More specifically, in the core back portion 22, the adhesive portions 41 are located at equal angular intervals around the circumferential direction of the core back portion 22, forming dots with an average diameter of 12 mm. More specifically, each adhesive portion 41 is located at the boundary between the core back portion 22 and the tooth portion 23. Adjacent adhesive portions 41 are spaced apart from each other. Furthermore, adhesive portions 41 are also located at the tip of each tooth portion 23, forming dots with an average diameter of 8 mm. By arranging the adhesive portions 41 as shown in FIG. 3, the core rigidity (mechanical strength) of the stator adhesive laminated core 21 can be ensured and the magnetic properties can be improved, as described below. In the example shown in FIG. 3, each adhesive portion 41 is located at both the tip of the tooth portion 23 and the boundary between the core back portion 22 and the tooth portion 23, but they may be located at either one of these positions. The average diameter shown here is an example, and can be appropriately selected from the range of 2 mm to 20 mm. Furthermore, the formation pattern shown in Figure 3 is an example, and the number and arrangement of each adhesive portion 41 can be appropriately changed as needed. Furthermore, the shape of each adhesive portion 41 is not limited to a circle, and may be a rectangle or other polygonal shape as needed.
[0030] The average thickness t2 of the adhesive joint 41 is set to 1.0 μm or more and 3.0 μm or less. If the average thickness t2 of the adhesive joint 41 is less than 1.0 μm, sufficient adhesive strength cannot be ensured. Therefore, the lower limit of the average thickness t2 of the adhesive joint 41 is set to 1.0 μm, more preferably 1.2 μm. Conversely, if the average thickness t2 of the adhesive joint 41 exceeds 3.0 μm, problems such as a significant increase in the amount of distortion of the magnetic steel sheet 40 due to shrinkage during thermal curing occur. Therefore, the upper limit of the average thickness t2 of the adhesive joint 41 is set to 3.0 μm, more preferably 2.6 μm, and most preferably 1.8 μm. The average thickness t2 of the adhesive portion 41 is the average value for the entire laminated core. The average thickness t2 of the adhesive portion 41 varies little with the stacking position along the stacking direction or the circumferential position around the central axis of the laminated core. Therefore, the average thickness t2 of the adhesive portion 41 can be determined by averaging values measured at 10 or more circumferential positions at the top end of the laminated core.
[0031] The average thickness t2 (μm) of the adhesive portion 41 and the average thickness t1 (μm) of the insulating coating have a relationship that satisfies the following formula 1. -4.3×t1+3.6≦t2≦-4.3×t1+6.9 (Formula 1)
[0032] Furthermore, it is preferable that the average tensile modulus E of the adhesive portion 41 is 1500 MPa to 4500 MPa, and the average tensile modulus E (MPa) and the average thickness t1 (μm) of the insulating coating satisfy the following formula 2. -5000×t1+4500≦E≦-5000×t1+9000 (Formula 2)
[0033] First, with regard to the above formula 1, if the average thickness t2 of the adhesive joint 41 is thinner than -4.3 × t1 + 3.6, the bond with the insulating coating will be weak, making it impossible to ensure adhesive strength and maintaining the mechanical strength of the stator core 21. On the other hand, if the average thickness t2 of the adhesive joint 41 is thicker than -4.3 × t1 + 6.9, the stress that the adhesive joint 41 exerts on the insulating coating will tend to reduce the adhesion between the insulating coating and the electromagnetic steel sheet 40. For these reasons, the average thickness t2 of the adhesive joint 41 is set within the range of formula 1.
[0034] Next, regarding the above formula 2, if the average tensile modulus E of the adhesive joint 41 is lower than -5000 × t1 + 4500, the bond between the adhesive joint 41 and the insulating coating will be weak, making it impossible to maintain adhesive strength, and there is a possibility that the mechanical strength of the stator core 21 will not be maintained. On the other hand, if the average tensile modulus E of the adhesive joint 41 is higher than -5000 × t1 + 9000, the stress that the adhesive joint 41 applies to the insulating coating will likely reduce the adhesion between the insulating coating and the electromagnetic steel sheet 40. For the above reasons, it is preferable that the average tensile modulus E of the adhesive joint 41 be within the range of formula 2.
[0035] The average thickness of the adhesive bonded portion 41 can be adjusted, for example, by changing the amount of adhesive applied. Furthermore, in the case of a thermosetting adhesive, the average tensile modulus E of the adhesive bonded portion 41 can be adjusted, for example, by changing one or both of the heating and pressurizing conditions and the type of curing agent applied during bonding.
[0036] Furthermore, for the reasons described above, it is more preferable that the average thickness t1 (μm) and the average thickness t2 (μm) further satisfy the following formulas 3 and 4. 0.7≦t1≦0.9 (Formula 3) 1.2≦t2≦2.6 (Formula 4)
[0037] In this embodiment, the plurality of electromagnetic steel sheets forming rotor core 31 are fixed to one another by caulking 42 (dowels) shown in Fig. 1. However, the plurality of electromagnetic steel sheets forming rotor core 31 may also have a laminated structure fixed by adhesive joints, similar to stator core 21. Furthermore, laminated cores such as the stator core 21 and the rotor core 31 may be formed by so-called rotational lamination. [Example]
[0038] The above-described stator core 21 was manufactured using the manufacturing apparatus 100 shown in FIG. 4 while changing various manufacturing conditions. First, the manufacturing apparatus 100 will be described. In this manufacturing apparatus 100, while electromagnetic steel sheets P are fed from a coil C (hoop) in the direction of arrow F, they are punched multiple times using dies arranged at each stage to gradually form the shape of electromagnetic steel sheets 40. Then, an adhesive is applied to the underside of the electromagnetic steel sheets 40, and the punched electromagnetic steel sheets 40 are stacked and pressurized while being heated. As a result, the adhesive hardens to form adhesive joints 41, completing the bonding.
[0039] As shown in Figure 4, the manufacturing apparatus 100 includes a first-stage punching station 110 located closest to the coil C, a second-stage punching station 120 located adjacent to the punching station 110 on the downstream side along the conveying direction of the electromagnetic steel sheet P, and an adhesive application station 130 located adjacent to the punching station 120 on the further downstream side. The punching station 110 includes a female die 111 arranged below the electromagnetic steel sheet P and a male die 112 arranged above the electromagnetic steel sheet P. The punching station 120 includes a female die 121 arranged below the electromagnetic steel sheet P and a male die 122 arranged above the electromagnetic steel sheet P. The adhesive application station 130 includes an applicator 131 having a plurality of injectors arranged according to an adhesive application pattern.
[0040] The manufacturing apparatus 100 further includes a lamination station 140 located downstream of the adhesive application station 130. The lamination station 140 includes a heating device 141, a female outer peripheral punching die 142, a heat insulating member 143, a male outer peripheral punching die 144, and a spring 145. The heating device 141, the outer periphery punching female die 142, and the heat insulating member 143 are disposed below the electromagnetic steel sheet P. On the other hand, the outer periphery punching male die 144 and the spring 145 are disposed above the electromagnetic steel sheet P. The reference numeral 21 denotes a stator core.
[0041] In the manufacturing apparatus 100 having the configuration described above, first, the electromagnetic steel sheets P are sequentially fed from the coil C in the direction of arrow F in FIG. 4. Then, the electromagnetic steel sheets P are first subjected to a punching process in a punching station 110. Next, the electromagnetic steel sheets P are subjected to a punching process in a punching station 120. Through these punching processes, the electromagnetic steel sheets P are given the shape of the electromagnetic steel sheet 40 having the core back portion 22 and the multiple teeth portions 23 shown in FIG. 3. However, since the electromagnetic steel sheets P are not completely punched at this point, they proceed to the next process in the direction of arrow F. In the next process, an adhesive application station 130, adhesive supplied from each of the injectors of an applicator 131 is applied in dots. Here, the adhesive is applied at the positions shown in FIG. 3.
[0042] Finally, the electromagnetic steel sheets P are sent to the lamination station 140, where they are punched out by a peripheral punching male die 144 and laminated with high precision. During this lamination, the electromagnetic steel sheets 40 are subjected to a constant pressure by a spring 145. By sequentially repeating the punching process, adhesive application process, and lamination process as described above, a predetermined number of electromagnetic steel sheets 40 can be stacked. Furthermore, the laminated core formed by stacking the electromagnetic steel sheets 40 in this manner is heated by a heating device 141 to a temperature of, for example, 200°C. This heating causes the adhesive to harden and form adhesive joints 41. Through the above steps, the stator core 21 is completed.
[0043] Using the manufacturing apparatus 100 described above, each of the stator cores 21 shown in No. 1 to No. 29 in Table 1A and Table 1B was manufactured. The chemical compositions of the electromagnetic steel sheets 40 used to manufacture each of the stator cores 21 were unified as follows. Note that the values of each component are all expressed in mass %. Si: 3.1% Al: 0.7% Mn: 0.3% Remainder: Fe and impurities
[0044] [Table 1A]
[0045] [Table 1B]
[0046] Specifically, multiple hoops (coil C) with the above chemical composition were fabricated. The thickness of the base steel for each hoop was standardized to 0.20 mm. An insulating coating solution containing metal phosphate and acrylic resin emulsion was applied to each hoop and baked at 300°C to form an insulating coating on both the front and back surfaces. The thickness of the insulating coating varied for each hoop. Specifically, as shown in Table 1A, the average insulating coating thickness t1 (μm) on one side was 0.1 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.4 μm, and 1.5 μm.
[0047] Then, by changing the hoop set in the manufacturing equipment 100, the type of adhesive applied to the electromagnetic steel sheet 40, the type of curing agent and curing accelerator added to the adhesive, and the coating thickness, multiple laminated cores (stator cores 21) were manufactured with different combinations of average thickness t1 of the insulating coating, type of adhesive, average thickness t2 of the adhesive portion 41, and average tensile modulus E, as shown in Table 1A.
[0048] Specifically, first, one of the hoops was set in the manufacturing apparatus 100. Then, while feeding out the electromagnetic steel sheet P from this hoop in the direction of arrow F in Fig. 4, it was punched out into a single-plate core (electromagnetic steel sheet 40) having a ring shape with an outer diameter of 300 mm and an inner diameter of 240 mm, and having 18 rectangular teeth 23, each 30 mm long and 15 mm wide, provided on the inner diameter side. Next, while the punched single plate cores were fed one after another, adhesive was applied in dots at each position shown in Figure 3, and the cores were then stacked and heated while being pressed at a predetermined pressure to harden them. The same process was repeated for 130 single plate cores to manufacture one laminated core (stator core 21). The same process was carried out for each hoop while changing the combination of conditions, thereby producing 29 types of laminated cores shown as No. 1 to No. 29 in Tables 1A and 1B.
[0049] As for the adhesive, a second-generation acrylic adhesive was used as an elastomer adhesive in Nos. 1 to 27 and 29. On the other hand, a general-purpose anaerobic adhesive was used as an anaerobic adhesive in No. 28. The average thickness t2 of the adhesive joint 41 was adjusted for each laminated core by changing the amount of application, and the average tensile modulus E of the adhesive joint 41 was adjusted for each laminated core by changing either or both of the heat and pressure conditions and the type of curing agent applied during bonding in the lamination station 140.
[0050] Each laminated core manufactured by the method described above was cut at a cross section including its axis. The average thickness t1 (μm) of the insulating coating was then determined. Furthermore, the average thickness t2 (μm) and the average tensile modulus E after curing of the adhesive joint 41 were determined. The average tensile modulus E was determined using the method described above. Furthermore, the outer diameter of each adhesive dot after curing was 5 mm on average. Then, the average thickness t1 (μm), the average thickness t2 (μm), and the average tensile modulus E (MPa) were substituted into the above-mentioned formulas 1 and 2 to determine whether or not the formulas 1 and 2 were satisfied. The results are shown in Table 1A.
[0051] Furthermore, the rigidity (mechanical strength) of the laminated core was also evaluated. Mechanical strength was evaluated by pressing a cutting edge with a width of 20 mm, a tip angle of 10°, and a radius of 0.15 mm against the laminated portion of the laminated core (between a pair of adjacent electromagnetic steel sheets 40) with increasing load, and measuring the magnitude of the load at which the laminated core cracked. The higher the load, the better, and loads of 4 MPa or higher were judged to be good or excellent. In Table 1B, for the mechanical strength of the laminated core, "excellent" indicates that high mechanical strength was ensured, "good" indicates that sufficient mechanical strength was ensured, and "poor" indicates that the minimum required mechanical strength was not met. Furthermore, the presence or absence of peeling of the insulating coating was also evaluated. In Table 1B, "none" indicates that there was no peeling at all, and "present" indicates that peeling occurred in some places. Furthermore, the magnetic properties of the laminated core were also evaluated. When evaluating the magnetic properties, the number of laminated sheets was set to 20, and the laminated core was covered with insulating paper before winding, and the core iron loss (W15 / 50 in Table 1B) was measured at a frequency of 50 Hz and a magnetic flux density of 1.5 tesla. Here, the number of laminated sheets of electromagnetic steel 40 used in the magnetic property evaluation was set to 20, as this gave almost the same results as when 130 sheets were used. The lower the core iron loss (W15 / 50 in Table 1B), the better, and a value of 2.70 or less was judged to be good or excellent. Regarding the magnetic properties of the laminated core in Table 1B, "excellent" indicates that high magnetic properties have been ensured, "good" indicates that sufficient magnetic properties have been ensured, and "poor" indicates that the minimum required magnetic properties are not met.
[0052] The relationship between the average thickness t1 of the insulating coating and the average thickness t2 of the adhesive joint 41 shown in Table 1A is shown in Figure 5. Similarly, the relationship between the average thickness t1 of the insulating coating and the average tensile modulus E of the adhesive joint 41 shown in Table 1A is shown in Figure 6.
[0053] As shown in Tables 1A and 1B, in the comparative examples shown in Nos. 16 and 17, the average thickness t1 of the insulating coating was small, and the magnetic properties were deteriorated. In addition, in the comparative example shown as No. 18, the unevenness of the insulating coating could not be completely filled, and the mechanical strength was reduced. In addition, in the comparative example shown as No. 19, the average thickness t2 of the adhesive portion 41 was large, and the proportion of the electromagnetic steel sheets 40 in the laminated core was reduced, resulting in a deterioration in magnetic properties. In addition, in the comparative example shown as No. 20, the unevenness of the insulating coating could not be completely filled, resulting in a decrease in mechanical strength. In addition, in the comparative example shown as No. 21, the average thickness t2 of the adhesive portion 41 was large, and the proportion of the electromagnetic steel sheets 40 in the laminated core was reduced, resulting in a deterioration in magnetic properties. In the comparative example shown as No. 22, the average thickness t2 of the adhesive portion 41 was small, and the adhesive strength was reduced, resulting in a decrease in mechanical strength. In addition, in the comparative example shown as No. 23, the average thickness t2 of the adhesive portion 41 was large, and the proportion of the electromagnetic steel sheets 40 in the laminated core was reduced, resulting in a deterioration in magnetic properties. In addition, in the comparative example shown as No. 24, the average thickness t2 of the adhesive portion 41 was small, and the adhesive strength was reduced, resulting in a decrease in mechanical strength. In addition, in the comparative example shown in No. 25, the average thickness t1 of the insulating coating was relatively thick and adhesion tended to be reduced, so the upper limit value of the average thickness t2 of the adhesive portion 41 (upper limit of the average tensile modulus E) was substantially reduced, and the mechanical strength was reduced. In addition, in the comparative example shown as No. 26, the average thickness t1 of the insulating coating was large, which reduced adhesion and caused the coating to peel off. In addition, in the comparative example shown as No. 27, the average thickness t1 of the insulating coating was large, which reduced adhesion and caused the coating to peel off. 5 and 6, the comparative example No. 28 used an anaerobic adhesive that did not have a sea-island structure, and therefore hardened adhesive joints 41 caused distortion in magnetic steel sheets 40. This distortion in magnetic steel sheets 40 resulted in a deterioration in the magnetic properties.
[0054] On the other hand, in the invention examples Nos. 1 to 15 and 29, the laminated core had high rigidity (mechanical strength), no peeling of the insulating coating, and the magnetic properties (W15 / 50) were confirmed to have the desired performance. In particular, because each adhesive joint was positioned as shown in Figure 3, i.e., in the position corresponding to the stator teeth, the core rigidity (mechanical strength) of the adhesive laminated core for the stator was ensured and the magnetic properties were improved. Among these invention examples, particularly in Nos. 3, 6, 8, 10, 12, 14, and 15, the average thickness t2 of the adhesive portion 41 was 1.8 μm or less, and therefore even higher magnetic properties than the other invention examples were obtained. Furthermore, among these, Nos. 6, 8, and 10 also have an average thickness t1 of the insulating coating that falls within the range of 0.7 μm to 0.9 μm. Therefore, they are optimized in terms of ensuring insulating performance and reducing performance degradation as a laminated core, making them the most preferable of all the inventive examples. In this embodiment, a thermosetting adhesive is applied, but the basic tendency is the same even if a room temperature curing adhesive is used.
[0055] Although one embodiment and examples of the present invention have been described above, the technical scope of the present invention is not limited to the above-described embodiment and examples, and various modifications can be made without departing from the spirit of the present invention. For example, the shape of the stator core 21 is not limited to the form shown in the above embodiment. Specifically, the outer and inner diameters of the stator core 21, the lamination thickness, the number of slots, the circumferential and radial dimensional ratio of the teeth portion 23, and the radial dimensional ratio of the teeth portion 23 to the core back portion 22, etc., can be designed as desired according to the characteristics of the rotating electric machine. In the rotor 30 in the above embodiment, a pair of permanent magnets 32 forms one magnetic pole, but the present invention is not limited to this. For example, one permanent magnet 32 may form one magnetic pole, or three or more permanent magnets 32 may form one magnetic pole.
[0056] In the above embodiment, a permanent magnet field type motor was used as an example of the rotating electric machine 10, but the structure of the rotating electric machine 10 is not limited to this, as exemplified below, and various known structures not exemplified below can also be adopted. In the above embodiment, a permanent magnet field motor has been described as an example of the rotating electric machine 10, but the present invention is not limited to this. For example, the rotating electric machine 10 may be a reluctance motor or an electromagnetic field motor (wound field motor). In the above embodiment, a synchronous motor is used as an example of an AC motor, but the present invention is not limited to this. For example, the rotating electric machine 10 may be an induction motor. In the above embodiment, an AC motor is used as an example of the rotating electrical machine 10, but the present invention is not limited to this. For example, the rotating electrical machine 10 may be a DC motor. In the above embodiment, an electric motor has been described as an example of the rotating electrical machine 10, but the present invention is not limited to this. For example, the rotating electrical machine 10 may be a generator.
[0057] In addition, within the scope of the spirit of the present invention, the components in the above-described embodiments may be replaced with well-known components as appropriate, and the above-described modifications may be combined as appropriate. [Industrial Applicability]
[0058] The present invention provides a stator bonded laminated core that can prevent peeling of the insulating coating and suppress deterioration of magnetic properties due to stress applied to the electromagnetic steel sheets by the bonded joint, and a rotating electric machine equipped with this stator bonded laminated core, and thus has great industrial applicability. [Explanation of symbols]
[0059] 10 Rotating Electric Machine 21 Laminated core (adhesive laminated core for stator) 40 Electrical steel sheet 41 Adhesive part
Claims
1. A bonded laminated core for a stator, comprising: a plurality of electromagnetic steel sheets each having a phosphate-based insulating coating on its surface and stacked coaxially; and adhesive portions provided between the electromagnetic steel sheets, The average thickness of the insulating coating is 0.3 μm to 1.2 μm, The average thickness of the adhesive joint is 1.0 μm to 3.0 μm, When the average thickness of the insulating coating is t1 in μm and the average thickness of the adhesive portion is t2 in μm, the following formula 1 is satisfied: The adhesive laminated core for a stator, wherein the adhesive portions are arranged at positions corresponding to the teeth of the stator. -4.3×t1+3.6≦t2≦-4.3×t1+6.9...(Formula 1)
2. 2. The adhesive laminated core for a stator according to claim 1, wherein the adhesive portion is disposed at at least one of the tip positions of the tooth portion and the boundary position between the core back portion and the tooth portion.
3. 3. The bonded laminated core for a stator according to claim 1, wherein adjacent bonded portions are spaced apart from each other.